Jawabanmu

2014-06-07T13:41:27+07:00
2 Fe(OH)3 + 3 H2SO4 → Fe2(SO4)3 + 6 H2O
1 2 1
2014-06-07T14:22:34+07:00

1 Fe(OH)3  +  a H2SO4  --->   b Fe2(SO4)3  + c H2O
unsur                       kiri                         kanan                 reaksi                 
Fe                            1                             2b                  b=1/2
S                              a                            3b                   a=3/2       
O                          3+4a                        12b+c                c=3
 H                          3+2a                          2c                   c=3

1 Fe(OH)3  +  3/2 H2SO4  --->   1/2 Fe2(SO4)3  + 3 H2O     
2 Fe(OH)3  +  3 H2SO4  --->    Fe2(SO4)3  + 6 H2O         
                                                                
1 4 1